2017
DOI: 10.1177/1534735417736133
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Homeopathic Treatment for Symptom Reduction in an Integrative Oncology Service

Abstract: Background: Homeopathy has the potential to reduce symptoms related to cancer treatment. The present study examined the feasibility of a homeopathic consultation and treatment program, provided as part of an integrative oncology service. Methods: The electronic medical files of patients undergoing a homeopathic consultation in an integrative oncology service clinic were examined retrospectively. Adherence to the homeopathic treatment regimen and perceived response to the treatment were evaluated. Results: The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
1
8
0
5
Order By: Relevance
“…Palliative care is an approach that improves the QoL of patients (adults and children) and their families in which homoeopathy can play a key role, with minimum or no adverse effects. Homeopathy can be successfully integrated in supportive care integrative oncology service [18][19][20] for palliative care, for better QoL, and to increase the chances of survival in cancer patients. Homoeopathic remedies can alleviate chemotherapy and radiation therapy side effects such as nausea, vomiting, fatigue, loss of appetite, depression, radiation-induced mucositis, and skin complaints.…”
Section: Discussionmentioning
confidence: 99%
“…Palliative care is an approach that improves the QoL of patients (adults and children) and their families in which homoeopathy can play a key role, with minimum or no adverse effects. Homeopathy can be successfully integrated in supportive care integrative oncology service [18][19][20] for palliative care, for better QoL, and to increase the chances of survival in cancer patients. Homoeopathic remedies can alleviate chemotherapy and radiation therapy side effects such as nausea, vomiting, fatigue, loss of appetite, depression, radiation-induced mucositis, and skin complaints.…”
Section: Discussionmentioning
confidence: 99%
“…Additiv zur leitliniengerechten Behandlung eingesetzte homöopathische Arzneimittel können z. B. bei Tumorerkrankungen den Allgemeinzustand signifikant verbessern und Nebenwirkungen der konventionellen Therapie lindern 22 , 23 , 24 , 25 , 26 , 27 , 28 .…”
Section: Konsensunclassified
“… 47 Clinical studies have shown homeopathy to potentially reduce many toxic effects of oncology treatments, while improving global health and well-being. 48 , 49 In a double-blind study of lung cancer patients, homeopathy was found to positively influence not only quality of life but also survival time. 50 , 51 …”
Section: Introductionmentioning
confidence: 99%